Invasive pulmonary aspergillosis - case report and review of literature - Ashutossh Naaraayan; Ronak Kavian; Jeffrey Lederman; Prasanta Basak; Stephen Jesmajian (Greater Baltimore Medical Center, 2015)
Invasive pulmonary aspergillosis (IPA) is a severe fungal infection with a high mortality rate. The incidence of IPA is on the rise due to an increase in the number of patients undergoing transplants and receiving chemotherapy and immunosuppressive therapy. Diagnosis is challenging due to the non-specific nature of symptoms. Voriconazole is the mainstay of therapy. We present a case of an elderly woman presenting with acute bronchitis and asthma exacerbation, who succumbed to overwhelming IPA. It is uncommon for IPA to develop in patients on short-term steroid therapy for asthma exacerbation. The possibility of aspergillosis in immunocompetent patients should be considered in those on systemic steroids and deteriorating pulmonary functions.